2016
DOI: 10.1074/jbc.c116.719989
|View full text |Cite
|
Sign up to set email alerts
|

GUN4-Protoporphyrin IX Is a Singlet Oxygen Generator with Consequences for Plastid Retrograde Signaling

Abstract: The genomes uncoupled 4 (GUN4) protein is a nuclear-encoded, chloroplast-localized, porphyrin-binding protein implicated in retrograde signaling between the chloroplast and nucleus, although its exact role in this process is still unclear. Functionally, it enhances Mg-chelatase activity in the chlorophyll biosynthesis pathway. Because GUN4 is present only in organisms that carry out oxygenic photosynthesis and because it binds protoporphyrin IX (PPIX) and Mg-PPIX, it has been suggested that it prevents product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…Gun4 lowers the magnesium concentration required for chelatase activity at low porphyrin concentrations (185) and substantially enhances the catalytic rate, by at least ten-fold (181). There are structures of apo-ChlH (186), apo-Gun4 (185,187,188), and Synechocystis sp. PCC 6803 Gun4 bound to both deuteroporphyrin (DIX) and Mgdeuteroporphyrin (Mg-DIX) (189); however, structures of sub-complexes, and the entire Mg chelatase complex at various stages of the catalytic cycle, will be required for a complete characterization of this important enzyme complex.…”
Section: The Transformation Of Protoix Into Chls -Chl Amentioning
confidence: 99%
“…Gun4 lowers the magnesium concentration required for chelatase activity at low porphyrin concentrations (185) and substantially enhances the catalytic rate, by at least ten-fold (181). There are structures of apo-ChlH (186), apo-Gun4 (185,187,188), and Synechocystis sp. PCC 6803 Gun4 bound to both deuteroporphyrin (DIX) and Mgdeuteroporphyrin (Mg-DIX) (189); however, structures of sub-complexes, and the entire Mg chelatase complex at various stages of the catalytic cycle, will be required for a complete characterization of this important enzyme complex.…”
Section: The Transformation Of Protoix Into Chls -Chl Amentioning
confidence: 99%
“…Alternatively, the EX1 pathway might be important in plant defense against pathogens [402,430]. 1 O 2 produced by Chl catabolites has been proposed to be involved in the hypersensitive response [431], and similarly to the flu-mutant [115], 1 O 2 produced by Chl catabolites has been suggested to initiate the EX1 pathway also in the wild type [432]. Interestingly, NADPH-protochlorophyllide oxidoreductases were shown to associate with EX1 and FtsH [425], though the interactions may be weak or transient, as they are not always observed [433].…”
Section: Signaling By 1 Omentioning
confidence: 99%
“…GUN4 was demonstrated to shield porphyrins from collisions with molecular oxygen that produce 1 O 2 ( Brzezowski et al, 2014 ), as was suggested previously ( Larkin et al, 2003 ; Verdecia et al, 2005 ). However, the subsequent finding that porphyrin-binding pocket of GUN4 is partially opened ( Chen et al, 2015 ) and that in vitro , porphyrins produce more 1 O 2 when they are bound to GUN4 ( Tarahi Tabrizi et al, 2016 ) indicates that GUN4 requires additional factors to shield porphyrins from collisions with molecular oxygen. Thus, GUN4 and GUN5 divert protoporphyrin IX from heme biosynthesis to chlorophyll biosynthesis by inserting a magnesium ion into protoporphyrin IX, yielding Mg-Proto.…”
Section: Gun2 Gun3 Gun4 Gun5 and Gun6mentioning
confidence: 99%